Work Pressure, Pay, and Burnout: A Study of Local and International Students in Taiwan - Yi-Chang Chen; Kai-Jui Liu; Yolanda Riska Lesmana (Jurnal Economia, 2026)
Balancing academic and work responsibilities is a common reality for working college students in Taiwan, often leading to emotional strain. This study examines the relationships among work pressure, compensation satisfaction, work-life balance, and burnout, with a focus on the mediating role of work-life balance. Grounded in Conservation of Resources (COR) theory, the research explores how resource dynamics affect well-being. Data collected from 403 Taiwanese and international students were analyzed using SPSS and SmartPLS. Results indicate that work pressure significantly increases burnout. Unexpectedly, for international students, satisfaction with compensation was positively associated with burnout, suggesting that higher pay may create additional pressure. Furthermore, work-life balance mediated these relationships for this group, but in the opposite direction. The findings highlight that addressing student burnout requires going beyond financial factors and urge institutions to provide practical support for managing dual demands.